Developing country implementation of multilateral environmental agreements The Philippine experience - Casis, Rommel J. (2017)
The establishment of Multilateral Environmental Agreements (MEAs) is absolutely necessary because environmental concerns cross boundaries. But despite their transnational reach, MEAs still rely on national governments to implement their provisions. This should not be a problem as under the customary norm of pacta sunt servanda, all states must comply with their international obligations in good faith. But the principle of common but differentiated responsibilities allow developingf states to have a standard of compliance different from developed countries. Thus, the question is: To what extent can the inyernational community reasonably expect developing countries to implement MEAs? To answer this question this paper examines the experience of the Philippines, a typical Asian developing state. By investigating the Philippine experience, this paper hopes to paint a picture of what could possibly be expected of developing countries when it comes to MEA implementation.
Keywords: Multilateral Environmental Agreements (MEA); Environmental agreements